Underwater topography determines critical breeding habitat for humpback whales near Osa Peninsula, Costa Rica: implications for Marine Protected Areas - Oviedo, L. (2008)
Migrating humpback whales from northern and southern feeding grounds come to the tropical waters near Osa Peninsula, Pacific of Costa Rica, to reproduce and raise their calves. Planning effective marine protected areas that encompass humpback critical habitats require data about which oceanographic features influence distribution during the breeding period. This study examines the relationship between water depth and ocean floor slope with humpback whale distribution, based on sightings during two breeding seasons (2005 and 2006). Data are from the Southern and Northern subpopulations in the Eastern Tropical Pacific (ETP). Analysis followed the basic principles of the Ecological Niche Factors Analysis (ENFA), where indices of Marginality and Tolerance provide insights on the restrictiveness of habitat use. At a fine scale, physical factors such as water depth and slope define the critical breeding and nursing habitat for M. novaeangliae. Divergence in the subsamples means of depths and slope distribution, with the global mean of the study area in both eco-geographical variables, determine habitat requirements restricted by topographic features such as depths ( < 100 m) and slope ( < 10%), and locate the key breeding and nursing habitat of the species within the continental shelf domains. Proposed Marine Protected Areas (MPA?s) network plans should consider connectivity of Caño Island?Drake Bay and the extension of Corcovado National Park maritime borders.